Knowledge Management: An Emerging Concept in Managerial Practice - Adhikari, Balaram; Adhikari, Bibhav (Administration and Management Review, 2009)
This article discusses the roles of knowledge management programs and, knowledge creation and transfer for increasing the effectiveness of organizational performance. The knowledge management tools that help the process of collecting and organizing the knowledge of groups of individuals have also been presented. The first part of the article is focused on the basic concept of Knowledge Management (KM). Specific areas covered in other parts include: (a) KM, a fad or fundamental concept? (b) an overview of the strategies used in the application of KM in professional organizations,(c) knowledge conversion process and its current practices, and (d) the technology to externalize knowledge through the creation of Knowledge base. Administration And Management Review Vol 20, No.2 August 2008 Page: 57-70